Method for synthesizing SSZ-13 molecular sieve through solid-phase crystal transformation
Through solid-phase transformation and crystallization synthesis method, the problem of difficulty in preparing SSZ-13 molecular sieve preparation in the prior art is solved, and the preparation of high crystallinity and high yield is achieved, reducing production costs and environmental pollution.
Patent Information
- Application Number
- CN202411728928.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-18
AI Technical Summary
The method of preparing SSZ-13 molecular sieve in the prior art cannot take into account the good performance of the molecular sieve and the problems of reducing costs and pollution. Moreover, the SSZ-13 prepared by solid phase method has a low crystallinity and poor catalytic performance.
The solid phase conversion synthesis method is adopted to prepare SSZ-13 molecular sieve through solid phase grinding, washing, drying and calcining steps to reduce the amount of template agent, reduce the use of solvent and water, and improve the crystallinity and yield.
The preparation of SSZ-13 molecular sieve with high crystallinity (up to 98%) and high yields has been achieved, reducing production costs and environmental pollution, and improving catalytic performance.
Smart Images

Figure CN119637891A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of green synthesis of molecular sieves, and in particular to a method for solid phase crystallization synthesis of SSZ-13 molecular sieves. Background Art
[0002] SSZ-13 molecular sieve is a microporous molecular sieve with CHA topological structure, which is composed of AlO4 and SiO4 tetrahedrons connected end to end through oxygen atoms and orderly arranged into double six-membered rings. These double six-membered rings are linked by some four-membered rings to form a three-dimensional pore structure with a maximum of eight-membered rings. SSZ-13 molecular sieve is widely used in diesel locomotive exhaust ammonia selective catalytic reduction (NH3-SCR) reaction, methanol to olefins technology (MTO) and carbon dioxide separation technology.
[0003] In the prior art, the method for preparing SSZ-13 usually adopts hydrothermal synthesis, which is a very mature method for preparing molecular sieves in industry with uniform system and high dispersion. However, in the synthesis process, a large amount of expensive organic templates such as N,N,N-trimethyl-1-adamantanammonium ion, benzyltrimethylammonium ion, N,N,N-dimethylethylcyclohexylammonium ion, etc. are used, which increases the cost and environmental pressure, and produces a large amount of wastewater and waste liquid. The yield of preparing molecular sieves by hydrothermal synthesis is low. With the improvement of environmental protection requirements, the demand for green synthesis of molecular sieves has been put on the agenda. At present, a solid phase method for preparing SSZ-13 molecular sieves has been proposed, but the resulting molecular sieve has low crystallinity and poor catalytic performance.
[0004] Therefore, a method for synthesizing SSZ-13 molecular sieve with high crystallinity and high yield through solid phase crystallization was developed to solve the technical defects of the existing method for preparing SSZ-13, which is that it cannot take into account both the good performance of molecular sieve and the reduction of cost and pollution. This problem has become an urgent problem to be solved by technicians in this field. Summary of the invention
[0005] Based on this, it is necessary to provide a method for solid phase crystallization synthesis of SSZ-13 molecular sieve with high crystallinity and high yield, in view of the technical defects of the existing technology for preparing SSZ-13, which cannot take into account the good performance of molecular sieves and reduce costs and pollution.
[0006] The present application provides a method for synthesizing SSZ-13 molecular sieve with high crystallinity and high yield through solid phase crystallization, the method comprising:
[0007] Step 1, solid phase grinding: molecular sieve, silicon source, alkali source, template agent and seed crystal are mixed, ground and mixed, and then heated under high pressure to react to obtain the first product;
[0008] Step 2, washing and drying: After the first product is cooled, it is washed to neutrality and dried to obtain the second product;
[0009] Step 3, calcination: the second product is calcined to obtain a product.
[0010] In one of the embodiments, the molecular sieve and the silicon source are fed in a ratio of SiO2 / Al2O3=1:(15-100) in molar parts.
[0011] In one of the embodiments, the molecular sieve and the silicon source are fed in a ratio of SiO2 / Al2O3=1:(15-50) in molar parts.
[0012] In one embodiment, the template and the silicon source are fed in a ratio of template / SiO2=(0.01-0.5):1 in molar parts.
[0013] In one embodiment, the ratio of the template to the silicon source satisfies the ratio of template / SiO2=(0.05-0.25):1, in molar parts.
[0014] In one embodiment, the template comprises: N,N,N-trimethyl-1-adamantyl ammonium halide and / or choline chloride.
[0015] In one embodiment, the molecular sieve includes one or more of USY molecular sieve, NaY molecular sieve and HY molecular sieve.
[0016] In one embodiment, the alkali source includes: sodium hydroxide and / or potassium hydroxide;
[0017] And / or, in terms of molar parts, the feed ratio of the alkali source and the silicon source satisfies the alkali source / SiO2=(0.01-0.3):1.
[0018] In one embodiment, the feeding ratio of the alkali source and the silicon source satisfies the ratio of alkali source / SiO2=(0.05-0.15):1 in molar parts.
[0019] In one embodiment, the seed crystal is SSZ-13 molecular sieve;
[0020] And / or, the feeding amount of the seed crystal is 0.05wt% to 5wt% of the raw material composition in parts by mass.
[0021] In one of the embodiments, the feed amount of the seed crystal is 1 wt% to 3 wt% of the raw material composition by weight.
[0022] In one embodiment, the silicon source includes: silica gel and / or sodium silicate.
[0023] In one of the embodiments, in step 1, the temperature of the high pressure heating is 150-220° C., and the time of the high pressure heating is 30-150 hours.
[0024] In one embodiment, in step 1, the temperature of the high pressure heating is 180-220° C., and the time of the high pressure heating is 48-72 hours.
[0025] In one embodiment, in step 2, the washing solvent is deionized water;
[0026] and / or,
[0027] In step three, the calcination temperature is 500-600° C., and the calcination time is 2-8 hours.
[0028] In one embodiment, in step 3, the calcination temperature is 500-550° C., and the calcination time is 3-6 hours;
[0029] The present application provides a method for synthesizing SSZ-13 molecular sieve by solid phase crystallization with high crystallinity, and the crystallinity reaches more than 98%.
[0030] In summary, the present application provides a method for synthesizing SSZ-13 molecular sieves with high crystallinity by solid phase crystallization, including: solid phase grinding, washing and drying, and roasting. In the technical solution provided by the present application, the molecular sieve is prepared by solid phase grinding, which can reduce the amount of template, and no additional solvent and water are required. While ensuring high crystallinity and high yield, no wastewater and waste liquid are generated, which simplifies the process and reduces production costs; it solves the technical defects of the prior art method for preparing SSZ-13 that cannot take into account both the good performance of the molecular sieve and the reduction of costs and pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0032] Figure 1 A schematic flow chart of a method for solid phase crystallization synthesis of SSZ-13 molecular sieve in the technical solution provided in the embodiment of the present application;
[0033] Figure 2 In the technical solution provided in the embodiments of the present application, the XRD diagrams of the SSZ-13 molecular sieve prepared in Example 1 and the reference product. DETAILED DESCRIPTION
[0034] The embodiments of the present application provide a method for synthesizing SSZ-13 molecular sieve through solid phase crystallization, which is used to solve the technical defects of the prior art method for preparing SSZ-13, which is unable to take into account both the good performance of molecular sieve and the reduction of cost and pollution.
[0035] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0036] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0037] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0038] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0039] In the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0040] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "upper", "lower", "left", "right" and similar expressions used herein are for illustrative purposes only and are not intended to be the only implementation method.
[0041] The following will be combined Figure 1 , a method for solid phase crystallization synthesis of SSZ-13 molecular sieve provided in an embodiment of the present application is prepared in a specific embodiment.
[0042] Example 1
[0043] Take HY (molecular sieve), sodium silicate nonahydrate (silicon source), N,N,N-trimethyl-1-adamantyl ammonium bromide (template) and sodium hydroxide (alkali source) as raw materials, grind and mix them according to the following molar ratio: SiO2 / Al2O3 (wherein the source of Al2O3 is molecular sieve) = 40; alkali source / SiO2 = 0.26; template / SiO2 = 0.03; the seed amount is 1% of the total weight, put into an autoclave, react at 160°C for 72 hours, and obtain a crystallized first product 1.
[0044] After the first product 1 is cooled to room temperature, it is washed with deionized water until it becomes neutral, and dried to obtain a second product 1.
[0045] After the second product 1 was calcined at 500° C. for 5 hours, an SSZ-13 molecular sieve product 1 was obtained. The crystallinity of the product 1 was 102.4% (the relative crystallinity was calculated by XRD diffraction pattern using the SSZ-13 molecular sieve with medium catalyst as a standard sample).
[0046] Figure 2 The XRD diffraction pattern of the SSZ-13 molecular sieve product 1 obtained in this example compared with the standard product is shown in FIG. Figure 2It can be concluded that the characteristic peaks of the SSZ-13 molecular sieve product prepared in this example are consistent with those of the standard product, and a SSZ-13 molecular sieve product that meets the composite standard specifications is obtained.
[0047] Example 2
[0048] Take USY (molecular sieve), silica gel (silicon source), choline chloride (template) and sodium hydroxide (alkali source) as raw materials and grind and mix them according to the following ratio: SiO2 / Al2O3 (wherein the source of Al2O3 is molecular sieve) = 50; alkali source / SiO2 = 0.28; template / SiO2 = 0.03; the amount of seed crystals is 2% of the total weight, put into an autoclave, react at 180°C for 60 hours, and obtain the crystallized first product 2.
[0049] After the first product 2 is cooled to room temperature, it is washed with deionized water until it becomes neutral, and dried to obtain a second product 2.
[0050] After the second product 2 was calcined at 550° C. for 5 hours, SSZ-13 molecular sieve product 2 was obtained. The crystallinity of product 2 was 100.2% (relative crystallinity was calculated by SCR diffraction spectrum using SSZ-13 molecular sieve with medium catalyst as standard).
[0051] Example 3
[0052] Use NaY (molecular sieve), silica gel (silicon source), N,N,N-trimethyl-1-adamantyl ammonium chloride (template) and sodium hydroxide (alkali source) as raw materials, grind and mix according to the following ratio: SiO2 / Al2O3 (wherein the source of Al2O3 is molecular sieve) = 20; alkali source / SiO2 = 0.16; template / SiO2 = 0.02; the seed amount is 1% of the total weight, put into an autoclave, and react at 190°C for 120h to obtain the crystallized first product 3.
[0053] After the first product 3 is cooled to room temperature, it is washed with deionized water until it becomes neutral, and dried to obtain a second product 3.
[0054] After the second product 3 was calcined at 600° C. for 2 hours, the SSZ-13 molecular sieve product 3 was obtained. The crystallinity of the product 3 was 106.5% (the relative crystallinity was calculated by SCR diffraction spectrum using the SSZ-13 molecular sieve with medium catalyst as the standard sample).
[0055] Comparative Example 1
[0056] HY (molecular sieve), sodium silicate nonahydrate, N,N,N-trimethyl-1-adamantyl ammonium bromide (template), sodium hydroxide (alkali source), and deionized water are used as raw materials and mixed and stirred according to the following ratios: sodium silicate nonahydrate / Al2O3 (wherein the source of Al2O3 is molecular sieve) = 40; OH - / SiO2=0.26; template / SiO2=0.03, 0.05, 0.08; H2O / SiO2=300; the amount of seed crystals is 1% of the total weight. After the gelation reaction, the purification reaction is carried out at 160°C for 100h.
[0057] The crystallized product was filtered and cooled to room temperature, then washed with deionized water until neutral. The dried intermediate product was calcined at 500°C for 5 hours to obtain the final product. According to the different template dosages R / SiO2=0.03, 0.05, 0.08, three products A, B and C were obtained respectively. Characterization showed that only sample C was pure phase SSZ-13 molecular sieve with a relative crystallinity of 92.3% (the relative crystallinity was calculated by SCR diffraction spectrum using SSZ-13 molecular sieve with medium catalyst as standard sample), and both A and B contained a large amount of impurities.
[0058] Comparative Example 2
[0059] Sodium silicate nonahydrate (silicon source), sodium aluminate, N,N,N-trimethyl-1-adamantyl ammonium bromide (template), and sodium hydroxide (alkali source) are used as raw materials and ground and mixed according to the following molar ratio: SiO2 / Al2O3 = 40; OH - / SiO2=0.26; R / SiO2=0.03; the seed amount is 0.01% of the total weight, loaded into an autoclave, reacted at 160°C for 100h, and a crystallized first control 2 was obtained.
[0060] After the first reference object 2 was cooled to room temperature, it was washed with deionized water until it was neutral, and dried to obtain a second reference object 2.
[0061] The second control 2 was calcined at 500°C for 5 hours to obtain a molecular sieve product D.
[0062] The product D was tested to be SSZ-13 molecular sieve with a yield of 80.2% and a crystallinity of 89.3% (the relative crystallinity was calculated by SCR diffraction pattern using SSZ-13 molecular sieve with medium catalyst as the standard sample), and contained a certain amount of impurities.
[0063] Comparative Example 3
[0064] Silica gel, sodium aluminate, choline chloride and sodium hydroxide are used as raw materials and ground and mixed according to the following molar ratio: SiO2 / Al2O3=40; OH - / SiO2=0.28; R / SiO2=0.03; without adding seed crystals, the mixture was put into an autoclave and reacted at 180°C for 72h to obtain a crystallized first control 3.
[0065] After the first reference object 3 was cooled to room temperature, it was washed with deionized water until it was neutral, and dried to obtain a second reference object 3.
[0066] The second control 3 was calcined at 500°C for 5 hours to obtain molecular sieve product E.
[0067] Product E is SSZ-13 molecular sieve with a relative crystallinity of 86.5% (the relative crystallinity is calculated by SCR diffraction pattern using SSZ-13 molecular sieve with medium catalyst as standard sample) and a relatively high content of impurities.
[0068] Test Case
[0069] This test example is to test the NH3-SCR reaction performance of the SSZ-13 molecular sieve samples prepared in Examples 1 to 3 and the comparative example.
[0070] Specific testing methods include:
[0071] 1) Molecular sieve ammonium exchange
[0072] The SSZ-13 molecular sieves prepared in Examples 1-3 and the comparative example were mixed in a ratio of ammonium chloride: molecular sieve: water (mass ratio) = 1:1:10, the pH was adjusted to 8-8.5, exchanged at 90°C for 1 hour under stirring, filtered, washed, dried, and then calcined at 550°C for 2 hours. The above process was repeated 3 times until the Na2O content in the molecular sieve was less than 0.1% (mass).
[0073] 2) Molecular sieve copper loading
[0074] Dissolve Cu(NO3)2 equivalent to 5% loading of molecular sieve CuO in 50 times water, add ammonium-exchanged molecular sieve under stirring, adjust pH to 8-8.5, filter, wash, dry, and calcine at 550°C for 4h.
[0075] 3) Catalytic reaction
[0076] The Cu-SSZ-13 molecular sieve prepared in Examples 1-3 and Comparative Examples after ammonium exchange and Cu loading was pressed into tablets, crushed, sieved, and hydrothermally aged at 650°C in a 10% H2O+90% air atmosphere for 100h. Then, 0.5g of a 40-60 mesh sample was taken and used for NH3-SCR reaction. The composition of the reaction mixture was: 1000ppmNO, 1100ppmNH3, 10Vol%O2, 10Vol%H2O, N2 as the balance gas, and the volumetric space velocity was 120000h. -1 The reaction temperature is 200℃~600℃, and the NO in the tail gas is detected online using MKS infrared gas analyzer x The test results are shown in Table 1.
[0077] Table 1
[0078]
[0079]
[0080] It can be concluded from Table 1 that the molecular sieve prepared by the technical solution provided in the embodiment of the present application has a good catalytic effect and has good catalytic performance compared with the control group; at the same time, less template is used in the preparation process, which effectively reduces the preparation cost and avoids environmental pollution; and no solvent needs to be added in the preparation process, resulting in less preparation waste.
[0081] In summary, the present application provides a method for synthesizing SSZ-13 molecular sieves by solid phase crystallization, including solid phase grinding, washing and drying, and calcination. In the technical solution provided by the present application, the molecular sieve is prepared by solid phase grinding, which can reduce the amount of template, and no additional solvent is required, no waste water is generated, and the production cost is reduced; it solves the technical defects in the prior art that the good performance of the molecular sieve cannot be taken into account while reducing costs and pollution.
[0082] The technical features of the above-mentioned embodiments can be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. At the same time, other implementation methods can be derived from the above-mentioned embodiments, so that structural and logical replacements and changes can be made without departing from the scope of this disclosure.
[0083] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A method for synthesizing SSZ-13 molecular sieve by solid phase crystallization, characterized in that: The method comprises: Step 1, solid phase grinding: molecular sieve, silicon source, alkali source, template agent and seed crystal are mixed, ground and mixed, and then heated under high pressure to react to obtain the first product; Step 2, washing and drying: After the first product is cooled, it is washed to neutrality and dried to obtain the second product; Step 3, calcination: the second product is calcined to obtain a product.
2. The method according to claim 1, characterized in that In terms of molar parts, the feed ratio of the template agent and the silicon source satisfies the ratio of template agent / SiO2=(0.05-0.25):
1.
3. The method according to claim 1 or 2, characterized in that: The template agent includes: N,N,N-trimethyl-1-adamantyl ammonium halide and / or choline chloride.
4. The method according to any one of claims 1 to 3, characterized in that: The molecular sieves include: USY molecular sieve, NaY molecular sieve and HY molecular sieve.
5. The method according to any one of claims 1 to 4, characterized in that: In terms of molar parts, the molecular sieve and the silicon source are fed to satisfy SiO2 / Al2O3=1:(15-100).
6. The method according to any one of claims 1 to 3, wherein the alkali source comprises: Sodium hydroxide and / or potassium hydroxide; And / or, in terms of molar parts, the feed ratio of the alkali source and the silicon source satisfies the alkali source / SiO2=(0.01-0.3):
1.
7. The method according to any one of claims 1 to 3, characterized in that: The seed crystal is SSZ-13 molecular sieve; And / or, the amount of the seed crystals added is 0.05% to 5% of the composition by mass.
8. The method according to any one of claims 1 to 3, characterized in that: The silicon source includes: silica gel and / or sodium silicate.
9. The method according to any one of claims 1 to 8, characterized in that: In step 1, the temperature of the high-pressure heating is 150 to 220° C., and the time of the high-pressure heating is 30 to 150 hours.
10. The method according to any one of claims 1 to 8, characterized in that: In step 2, the washing solvent is deionized water; and / or, In step three, the calcination temperature is 500-600° C., and the calcination time is 2-8 hours.